Determination of Shear Wave Splitting Parameters in 2018 Lombok Earthquake Using Rotation Correlation Method: Preliminary Result. Issue 1 (October 2021) - Sasmi, Annisa Trisnia; Nugraha, Andri Dian; Muzli, Muzli; Widiyantoro, Sri; Zulfakriza, Zulfakriza; Wei, Shengji; Sahara, David P; Puspito, Nanang T; Priyono, Awali; Afif, Haunan; Supendi, Pepen; Daryono, Daryono; et al.
Abstract: Shear-wave splitting (SWS), or the propagation of two independent shear waves, can be used as an indicator of seismic anisotropy. In this study, we utilize this concept using aftershock data of the 2018 Lombok earthquake which had been acquired in period of August 4 – September 9, 2018. The goal of this research is to better understand the crack distribution related to the rupture zone of the 2018 Lombok earthquake. After applying instrument correction to the data, the waveform data were then windowed in each P and S arrival time. To determine the SWS parameters, we performed rotation in each horizontal seismogram components. The horizontal components were rotated from azimuth 0° to 180° with an increment of 1°. Cross-correlation coefficient (CCC) was determined for each rotation angle. The polarization direction and the SWS delay time were chosen from the parameters shown in the highest value of CCC.